Challenges and good practices in STEM: A systematic review and implications for higher education institutions - Christou, Eirini; Parmaxi, Antigoni; Economides, Anastasios A.; Perifanou, Maria; Manchenko, Maryna; Mazaj, Jelena (My University, 2022)
This study maps the challenges and good practices applied in the real life of Science, Technology, Engineering, and Mathematics (STEM) professionals. We conducted a systematic review selecting published manuscripts between 2018 and 2021. The search strategy included a systematic search in two well-known online databases which are related to STEM, ProQuest and Scopus. After the application of the inclusion and exclusion criteria, 35 papers were included in the dataset. The review demonstrated the challenges and good practices in STEM careers which include personal challenges and good practices for STEM professionals; challenges and good practices encountered at the workplace; and challenges and good practices at social and public space in general. Findings demonstrate that there are still challenges encountered by professionals, especially women and minorities, in STEM fields, but there are also some good practices that can reduce the barriers and help overcome those challenges. The paper concludes with implications for practitioners and suggestions for future research.
Keywords: Educational institutions; Management training; Professional aspects; STEM